2014
DOI: 10.1177/1035304614556040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring recent increases in the gender wealth gap among Australia’s single households

Abstract: This study uses three wealth modules from the Household, Income and Labour Dynamics in Australia Survey to explore the gender wealth gap for single Australian households between 2002 and 2010. The findings indicate a significant gender wealth gap, which has increased over the 8 years explored. Most of the increase in the wealth gap was associated with a relatively rapid increase in the value of housing assets by single men over the study period. The findings of this study challenge a wider literature that tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Austen et al . (2015) found that the gender wealth gap for single‐headed Australian households between 2002 and 2010 was driven by rapid increases in housing prices and suggested that greater male willingness to invest in risky assets such as shares was not the main contributor for this time period.…”
Section: Underlying Causes Of the Gender Superannuation Gapmentioning
confidence: 99%
“…Austen et al . (2015) found that the gender wealth gap for single‐headed Australian households between 2002 and 2010 was driven by rapid increases in housing prices and suggested that greater male willingness to invest in risky assets such as shares was not the main contributor for this time period.…”
Section: Underlying Causes Of the Gender Superannuation Gapmentioning
confidence: 99%
“…Other forms of financial wealth also feature a strong gender divide. For example, 2010 Household, Income and Labour Dynamics in Australia (HILDA) Survey wealth data for single men and women aged 55+ show a 79 per cent gender gap (favouring men) in the net value of business assets and a 25 per cent gap in the net value of financial instruments (Austen et al , Table 1).…”
Section: The Gender Gap In Retirement Income Savings and Wealthmentioning
confidence: 99%
“…Significant social disadvantage in later life for women is linked to poorer employment outlooks analyses below and also to women’s lower levels of wealth relative to men as documented by Austen et al (2014). One aspect of the income and wealth differential is women’s significantly lower level superannuation holdings, resulting from their lower capacity for contributions across the life course (Australian Institute of Superannuation Trustees, 2014: 7).…”
Section: Discussionmentioning
confidence: 99%
“…This article explores structural barriers to women’s employment equality and the reasons why the policy requirement to work until one’s late 60s may be difficult for many to achieve. Paradoxically, women need to work longer than men of a similar age because of a gender wealth gap that includes, but goes beyond, a pay and income gap (Austen et al, 2014). This accumulating gap in economic assets translates to a smaller pool of resources available to supplement public pensions which are under pressure in the age of austerity.…”
Section: Introductionmentioning
confidence: 99%